SENTIMENT ANALYSIS OF THE REPUTATION OF THE GLOBAL TRAINING AND TEST CENTER (GTTC) SUKABUMI - Taufik Nurhadi; Hesri Mintawati; Yusuf Iskandar (RADJA PUBLIKA, 2026)
The reputation of a global training institution is an important factor in increasing competitiveness and public trust in the quality of services provided. The Global Training and Test Center (GTTC) Sukabumi, as a global-based training and certification institution, has various sources of feedback from participants, partners, and stakeholders, most of which are in the form of unstructured text data. This study aims to analyze sentiment towards the reputation of the Global Training and Test Center (GTTC) Sukabumi using a text mining-based sentiment analysis approach. Research data were obtained from participant reviews, testimonials, and stakeholder comments collected through interviews and documentation. The method used is sentiment analysis with the help of Orange Data Mining software to classify sentiment into positive, negative, and neutral, and identify key topics that influence the institution's reputation. The results of this study are expected to provide an overview of public perception towards GTTC and become a basis for strategic decision-making to improve the quality of service and the institution's global reputation.